HUBUNGAN ANTARA PENERIMAAN DIRI DAN RELIGIUSITAS TERHADAP KUALITAS HIDUP PADA WANITA LANJUT USIA - , ERNI HESTININGRUM, Prof (ret). Dr. Sartini Nuryoto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aimed to determine whether there is a positive and significant relationship between self acceptance, and religiosity on quality of life in older women in the sub district of Pundong on year 2011. Determination of the subject in this study is using purposive sampling.Total sampling is 109 elderly. The measurement instrument used in this study consisted of quality of life scale, self-acceptance scale and the scale of religiosity. Before conduct this study, the first is study to the validity test of the instrument on 30 elderly. The validity test is using product moment technique, and the coefficient alpha was used to test reliability. To scale the quality of life found reliability coefficients of (rtt) 0.933, found selfacceptance scale reliability coefficient of (rtt) 0.934 and for the religiosity scale reliability coefficient was found for (rtt) 0.937. Next to the data analysis used multiple regression techniques. The results of this study indicate that: (1) self-acceptance, and religiosity are able to predict the quality of life (Freg = 61.588 and p = 0.00, p <0.05) significant results, further showed that the Self Acceptance and Religiosity in a joint - the same contributes on the Quality of Life is 54.5%, Self Acceptance contribution is greater than the Religiosity of the quality of life that is RÂ² = 552 or 55.2%, while the predictor Religiosity contributes 52.1% or RÂ² = 521, (2) There is a relationship a positive association between self-acceptance elderly with quality of life, significant value (p) for self-acceptance variable indicates the value of 0.00 (p <0.05), (3) There is a positive relationship between religiosity elderly with quality of life of elderly. Significant value p for the religiosity variable shows the value 0.00 ( p < 0.05)